CRISPR/Cas9-mediated editing of PHYTOENE DESATURASE gene in onion (Allium cepa L.) - Mainkar, Pawan; Manape, Tushar Kashinath; Satheesh, Viswanathan; Anandhan, Sivalingam (Frontiers in Plant Science, 2023)
Clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 is a precise genome-editing tool used to introduce genetic modifications in a wide range of crop species. Thus far, there is no report of CRISPR/Cas9mediated genome editing in onion (Allium cepa L.). In the present study, we targeted two exons of the gene coding for Phytoene desaturase (AcPDS) in onion cv. Bhima Super. The sgRNA-carrying constructs were cocultivated with 8-week-old embryogenic calli using an Agrobacterium-mediated transformation protocol and incubated on the media without hygromycin B selection. Out of the total 617 co-cultivated calli, 21 (3.4%) regenerated shoots exhibited three distinct phenotypes; albino, chimeric, and pale green; in comparison to the wild-type non-transformed regenerated shoots. Total chlorophyll content was drastically reduced in albino shoots and significantly decreased in chimeric shoots. Out of the six PCR-confirmed regenerated shoots, two exhibited the albino phenotype due to indels and substitution-based mutations in and around the AcPDS target sites. Deep amplicon sequencing revealed a significantly variable indel frequency between two sgRNAs, ranging from 1.2% to 63.4%, along with a 53.4% substitution frequency. The mutation of the AcPDS gene generated a visually detectable albino phenotype, thus confirming successful editing of the AcPDS gene. This is the first time a CRISPR/Cas9-mediated genome editing protocol has been successfully established in onion, with the AcPDS gene serving as an example. This study will provide the necessary momentum for researchers to further basic and applied research work on onions.